FLT3LG and IFITM3P6 consolidate T cell activity in the bone marrow microenvironment and are prognostic factors in acute myelocytic leukemia - Chen, Haiyan; Wu, Meng; Xia, Hongping; Du, Songjie; Zhou, Guoren; Long, Guangfeng; Zhu, Yanan; Huang, Xu; Yang, Daheng (Frontiers in Immunology, 2022)
Acute myelocytic leukemia (AML) is a malignancy of the stem cell precursors of the myeloid lineage. CD4+ and CD8+ T cells play pivotal roles in influencing AML progression but are functionally suppressed in the bone marrow microenvironment. We aimed to find hub genes related to T cell exhaustion and suppression, thereby providing evidence for immunotherapy. In this study, gene transcriptome expression data from TCGA and TARGET databases were utilized to find key genes. Firstly, CIBERSORT immune cell infiltration algorithm and WGCNA method were used to identify CD4+ and CD8+ T cells-related genes. Univariate and multivariate cox regression analyses were then introduced to construct the overall survival prognosis model and included hub genes. The ESTIMATE and ssGSEA scoring methods were used to analyze the correlation between the hub genes and immune activity. Single-cell transcriptome analysis was applied to detect the immune cells expressing hub genes, hence, to detect exact mechanisms. Consequently, FLT3LG and IFITM3P6 were determined to be positively correlated with patients’ overall survival and microenvironment immune activity. Further study suggested FLT3-FLT3LG and IFITM3P6-miR-6748-3p-CBX7 signaling axes were involved in CD4+ and CD8+ T cells activation. This may be one of the mechanisms of T cells suppression in AML.